The discussion strategy in strengthening environmental awareness - Santacruz Espinoza, Atanacia (2018)
The discussion strategy opens a horizon of reflection, in terms of the preservation of the environment and man-nature interaction. The general objective research was to demonstrate the impact of the Discussion Strategy in the strengthening of environmental awareness in the students of II Initial Education cycle by National Intercultural University of La Amazonia, Pucallpa. The quantitative and qualitative approach and the pre-experimental design were used. The instrument was the questionnaire. The impact of the Discussion Strategy in strengthening environmental awareness was significant with (p <0.05). Supported with the qualitative study research with improvements in ecological responsibility, destination of the planet, even more its sustainability. This is achieved through the dialogue guided by the argumentation process, in order to generate preventive interventions in the solution of problems; with the understanding that the participant is part of a great whole called environment, and that he must protect it. To affirm it, it corroborates Aldous Huxley's thought: "The conscience is only possible through the change; the change is only possible through movement".